HUBUNGAN ANTARA KECEPATAN REAKSI, KELINCAHAN, DAN KESEIMBANGAN TERHADAP KEMAMPUAN MENGGIRING BOLA PADA SISWA SSB MARS MARGOYOSO KALINYAMATAN JEPARA TAHUN 2023 - Dwi Muryadi, Agustanico (JURNAL ILMIAH PENJAS (Penelitian, Pendidikan dan Pengajaran), 2024)
The objectives of this study are: (1) to determine whether there is a relathionship between reaction speed, agility, and balance on the ability to dribble in students of Football School Mars Margoyoso Kalinyamatan Jepara in 2023, (2) to determine the ability to dribble in students of Mars Margoyoso Football School Margoyoso Kalinyamatan Jepara 2023. The research method used is descriptive with a correlation test with the test technique used to measure the effect of reaction speed, agility, and balance one the dribbling ability of Mars Margoyoso Football School students. The population used is 15 students. The results of the analysis show: (1) there is no relationship between reaction speed and dribbling ability in Mars Margoyoso Football School students with a value of rx1y = 0.189< r(0.05)(13) = 0.5140. (2) there is no relationship between agility and dribbling ability in Mars Margoyoso Football School students with a value of rx2y=0.053<r(0.05)(13) =0.5140 . (3) there is no relationship between balance and dribbling ablity in Mars Margoyoso Football School students with a value of rx3y=0.213<r(0.05)(13)= 0.5140. (4) there is no relationship between reactions speed, agility, and balance on the ability to dribble in Mars Margoyoso Football School students with a value of ry(x1.x2.x3)= 13.575< r(0.05)(13) = 0.5140.